The Tradition of Ascending the Sacred Cave: Paying Homage to Great-Grandfather (Thuat) of Wang Ching Mountain and the Beliefs of Southern Thai Buddhists in Honoring Sacred Mountain Deities in the Community of Khok Muang Subdistrict, Khlong Hoi Khong District, Songkhla - Phannarat, Jirawitt; Phookwanthong, Jirapat; Petarwut, Songpop; Songkhro, Jirayu (Journal of Humanities and Social Sciences Loei Rajabhat University, 2024)
The worship of great-grandfather (Thuat) on Wang Ching mountain and the passing down of this tradition hold significance as an expression of respect and faith toward sacred forces that Southern Thai Buddhists believe protect their community. Additionally, the continuation of this tradition strengthens community unity through shared rituals, food offerings, and the transmission of beliefs to future generations, helping to preserve this valuable heritage. Therefore, the objectives of this research were: 1) to study the significance of the tradition of ascending the sacred cave, known as “Paying Homage to Great-grandfather of Wang Ching Mountain,” and its influence on the beliefs of people in community regarding the sacredness on mountain, 2) to investigate the perpetuation of these beliefs and their impact on the livelihoods of people within the community. The study employed a qualitative research methodology to investigate the phenomenon. The key informants were 20 local residents and 6 persons hold official positions within the community. This includes village leaders, subdistrict administrators, and local government organizations by using snowball sampling method. Data were conducted by using non-participatory observation, in-depth interviews, and group discussions. Audio recording device, notebook for note-taking, and camera for capturing photographs were utilized in the data collection procedures taken place in Khok Muang community, Klong Hoi Khong District, Songkhla Province. The results revealed that in the past, people in the community held a deep belief in the sacredness of mountains, viewing them as comparable to guardian deities of the village. With their belief and devotion, the community members joined forces and embarked on a journey to circumambulate the mountain, engaging in a significant ritual of offering food to the monks. This annual tradition is held with great reverence towards the protective and wish-fulfilling powers of the sacred entities. The preservation of this belief is achieved through the oral tradition of passing down the knowledge of the tradition of ascending the cave of Wang Ching Mountain through storytelling from generation to generation.